How COVID-19 quarantine(s) can generate poverty? - Mario Arturo Ruiz Estrada (Contemporary Economics, 2021)
This research paper attempts to show visually how the COVID-19 quarantines can generate massive unemployment, constant expansion of inflation, reduction of the purchasing power parity, and poverty expansion from a multidimensional perspective. This visualization is only possible by creating a new multivariate graphical modeling called "The Multidimensional Poverty Kaleidoscope Graph." The multidimensional poverty kaleidoscope graph is not intended to use a forecasting model in any case. However, its application is not limited to the study of a particular group of countries. It is not constrained by issues about the region or countries interested in applying the multidimensional poverty kaleidoscope graph. There are four primary phases in the implementation of the multidimensional poverty kaleidoscope graph. The first phase is the design of the input-output-table. The second phase is divided into two sections of analysis: the first section of analysis assumes that the COVID-19 quarantine time framework growth rate (Y = Independent variable) impacts directly on our four variables in analysis, such as the inflation growth rate (X1); the unemployment growth rate (X2); purchasing power parity growth rate (X3); the government budget deficit (X4). In the second section of the analysis, the last past four variables in analysis became our dependent variables and directly affected the poverty growth rate (Z). The third phase is the construction of the multidimensional poverty kaleidoscope graph. Finally, the multidimensional poverty kaleidoscope graph was applied to three countries, such as the U.S., Malaysia, and Guatemala.
Keywords: I32; 330; Poverty; policy modeling; poverty indicators; economic development; graphs